2019
DOI: 10.1590/s0004-2803.201900000-34
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, Vitamin D and Nutritional Status in Patients With Advanced Colorectal Cancer or During Follow-Up

Abstract: BACKGROUND: Considering the high incidence of colorectal cancer (CRC) related deaths, many studies have investigated variables that can affect survival, with the aim of prolonging survival. The nutritional status can also be predict survival in patients with CRC. OBJECTIVE: The aim of the present study was to evaluate if BMI, %FAT, PhA, PG-SGA, adiponectin levels, and vitamin D levels are relevant to the characterization and differentiation of patients with advanced CRC and patients with a history of CRC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Moreover, higher blood LEP concentration was associated with radical tumor excision and higher TNFalpha with nonsurgical perioperative complications. Our study corroborates the work by Cavagnari et al [8], who show that BMI, FM, vitamin D, and blood ADP concentration are not significant prognostic factors in CRC patients undergoing surgery. However, the other reference data do not provide clear evidence of associations between obesity, adipocytokine level, and CRC surgery outcomes, for either colon or rectal tumors [2].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, higher blood LEP concentration was associated with radical tumor excision and higher TNFalpha with nonsurgical perioperative complications. Our study corroborates the work by Cavagnari et al [8], who show that BMI, FM, vitamin D, and blood ADP concentration are not significant prognostic factors in CRC patients undergoing surgery. However, the other reference data do not provide clear evidence of associations between obesity, adipocytokine level, and CRC surgery outcomes, for either colon or rectal tumors [2].…”
Section: Discussionsupporting
confidence: 93%
“…Obesity is also associated with an increased risk of CRC-related mortality [1], although some authors have shown that the association between cancer treatment outcome and body weight is J-shaped (the "obesity paradox") [5]. Adipocytokines, which are hormonal substances secreted by adipocytes, have been proposed as one of the potential mediating factors in the association between patient nutritional status and the risk of carcinogenesis [6][7][8], CRC surgery outcomes (lymph node retrieval, margins, recurrence, survival, etc.) [2,9,10], perioperative complications [11], infection [12], response to chemotherapy [13], chemotherapy-associated hepatotoxicity due to liver steatosis [2], and the risk of neoplasmatic cachexia and frailty [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, if uptake of plasma insulin by peripheral tissue elevates, a reduced risk of CRC can be expected (16). Consequently, more studies on hormone adiponectin and its association with cancer are required (17,18). Adiponectin has revers correlation with obesity and hyperinsulinemia and insulin resistance (15,19).…”
Section: Introductionmentioning
confidence: 99%